Sistem Pendukung Keputusan Penerima Bantuan Sosial Program Keluarga Harapan (PKH) Kelurahan Titi Kuning Dengan Metode VIKOR - Sianipar, Putri Nopriani; Cipta, Hendra (STIKOM Tunas Bangsa Pematangsiantar, 2023)
To increase the effectiveness of poverty alleviation in the field of social protection, the Indonesian government, starting in 2007, is implementing the Program Keluarga Harapan (PKH). The Program Keluarga Harapan (PKH) has been implemented in various regions in Indonesia, and Titi Kuning Village, Medan Johor District, Medan City, North Sumatra is one of the areas in Indonesia that has implemented PKH. The obstacle that is often found in the process of determining PKH beneficiaries is that there are beneficiaries of PKH social assistance who are not on target. In addition, many families, ranking the determination of PKH beneficiaries will take a long time. Thus a solution is needed to help this problem, namely with a decision support system that applies the VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method as determining priority for prospective recipients of PKH social assistance in Titi Kuning Village. Decision support systems have the goal of providing information to decision-makers so that decision-makers can make more effective and targeted decisions. Designing a decision support system for prioritizing prospective recipients of PKH social assistance using the VIKOR method in the Titi Kuning Village, so that PKH assistance recipients are right on target according to predetermined criteria. It can support the performance of the Village Government to the Social Office and to the Ministry of Social Affairs.